PENERAPAN QUIZ TEAM UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS X-6 SMA NEGERI I IMOGIRI - Rina Zunita; Benedictus Kusmanto (Universitas Sarjanawiyata Tamansiswa, 2015)
the purpose of this research is to improve the activity and achiefement of student to learn mathematic using cooperative learning model type Quiz Team in class X 6 SMA N I Imogiri. The type of this research is classroom action research with collaboratively. The subject of this observation is the students in class X 6 SMA N I Imogiri it consist of 32 students. The object of this research is activity and achievement of student to learn of mathematic by using cooperative learning model type Quiz Team. The result of this research shows that the activity and achievement of student increased after applying cooperative learning model type Quiz Team. The activity of learning process increased from cycle 1 56.4% to cycle II 71.61%. Beside that the subjection of student’s achievement has a increase in pre cycle shows 64.7I with Minimum Completeness’ Criteria ‘KKM is 43.75%. In average, the final examination from cycle I 74.58 with KKM 52.50%. The final examination in cycle II is 84.56 with KKM 87.50. See this result of final examination cycle I and cycle II using cooperative learning model type Quiz Team, the teacher are hoped to apply cooperative learning model type Quiz Team in learning process.